Preparation and Characterization of Activated Carbon From Mangosteen Peels (Garcinia Mangostana L) - Rahmiatul Husna; Ananda Putra (Departemen Kimia FMIPA UNP, 2020)
The purpose of this experiment was to prepare and characterize activated carbon from Mangosteen peels (Garcinia mangostan L). Carbon from Mangosteen peels was prepared by pyrolysis method at 300°C for 1 hour. This carbon was activated by chemical activation process with various activating reagent and concentration. The activated carbon was characterized using Indonesian Industry Standard (SNI 06-3730-1995), that is maximum water content of 15%, maximum vapor content of 25%, maximum ash content of 10% and bounded carbon content at least 65%. The results showed that the highest bounded carbon content obtained from pyrolysis was 78,09%. The best activating reagent was HCl with concentration of 4N that improved the bounded carbon to 87,84%. The water content, ash content, and vapor content of activated carbon was obtained as follows, 6,11%, 1,97%,and 10,19%. Based on this results, activated carbon of mangosteen peels conformed the (SNI 06-3730-1995) values and will be applied as a thermoelectric material.